Solidum: a seer of Southeast Asia and beyond. (4th May 2018) - Naval, Jaime B.
ABSTRACT: For academics, a collaborative undertaking without great funding and with no promise of enviable remuneration is exciting enough a challenge to carry out. It is de facto a call of duty to contribute to a compendium that would preserve and promote the political, patriotic, policy and principled ideas of distinguished Filipino thinkers in the 20th century. Prof. Estrella "Estring" Solidum belongs to this exceptionally perceptive group. Solidum the "seer" was a pioneering scholar of Southeast Asia and of security studies. Among others, she diligently dissected ASEAN's "functional regionalism", presciently offered an alternative definition of security, and solicitously insisted on "bioglobalism" as a construct that encompasses global cooperation for the conservation of life.